The Effect of "Unclassified" Blood Pressure Phenotypes on Left Ventricular Hypertrophy - Belde Kasap-Demir; Cemaliye Başaran; Tülay Demircan; Gökçen Erfidan; Özgür Özdemir-Şimşek; Seçil Arslansoyu-Çamlar; Demet Alaygut; Fatma Mutlubaş; Cem Karadeniz (AVES Yayincilik, 2024)
Objective: We aimed to evaluate the clinical significance of the "unclassified" blood pressure phenotypes on left ventricular hypertrophy in children. Materials and Methods: All children evaluated with ambulatory blood pressure monitoring in the pediatric nephrology department between October 2018 and January 2021 were included in the study. Prehypertension, normotensive, white coat hypertension, masked hypertension, ambulatory hypertension groups and 2 other groups including increased blood pressure load, normal ambulatory blood pressure measurements, but normal (unclassified group 1) or high (unclassified group 2) office blood pressure measurements were defined according to the American Heart Association 2014 statement. Left ventricular mass index, left ventricular mass index/95 percentile values, and left ventricular hypertrophy ratios were compared between the groups separately to establish the influence of the unclassified cases. Results: A total of 497 children were included. There were 52 cases in normotensive, 47 cases in unclassified group 1, 50 cases in masked hypertension, 79 cases in white coat hypertension, 104 cases in unclassified group 2, and 165 cases in the ambulatory hypertension group. Left ventricular mass index/95 percentile and left ventricular hypertrophy in masked hypertension were significantly higher than normotensive but similar between normotensive and unclassified group 1 groups. Left ventricular hypertrophy was significantly higher in the ambulatory hypertension group compared to white coat hypertension, and similar between white coat hypertension and unclassified group 2 groups. Conclusion: Independent of age, we have found that interpretation of blood pressure load not only has a limited predictable effect on left ventricular hypertrophy but also causes a large group of patients to be unclassified.